The Historical Film as a Field, a Mode of Thought (Historying) and a Pack of Tricks We Play Upon the Dead, History is . . . a pack of tricks which we play upon the dead” – Voltaire - Rosenstone, Robert (Revista Calarma, 2023)
Some forty years ago I wrote my first essay on historical (history) film. At the time, the field of history almost totally ignored the visual media. In the early eighties of the last century, the few historians who wrote about film did so as part of a traditional topic – such as the history, or economics, or cultural impact of the motion picture industry. Historical journals did not review history films, and any historian who considered a dramatic feature as a possible way of understanding the past would have been considered not to be a serious member of the profession.